2018
DOI: 10.1002/iub.1980
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of abrin‐mediated inhibition of protein synthesis and apoptosis

Abstract: The plant toxin, abrin, a type‐II ribosome inactivating protein, is extremely lethal, the human fatal dose being ~1 μg/kg body weight. Abrin has been classified as an agent for bioterrorism, which is of concern. Conversely, the high toxic property of abrin has been employed in generating immunotoxins, whereas its toxin moiety is conjugated to cell surface marker‐specific antibodies for cell‐targeted killing. Different cell types exhibit variable levels of sensitivity to abrin toxicity; therefore, adequate know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It appears that both the intrinsic and the extrinsic pathway are involved in stenodactylin-induced cell death, reinforcing the idea that RIPs induce a complex response in intoxicated cells triggering multiple death pathways (Polito et al, 2009;Pervaiz et al, 2016). Furthermore, it has been recently reported that abrin, another type 2 RIP, can trigger cell death through many mechanisms in different cell lines (Tiwari and Karande, 2019). Stenodactylin treatment induces the disruption of mitochondrial membrane potential, as confirmed by JC-1 positive staining at 24 h. RIP-triggered mitochondria-associated apoptotic signaling was also previously described (Narayanan et al, 2005;Sikriwal et al, 2008;Bora et al, 2010;Polito et al, 2016c).…”
Section: Discussionmentioning
confidence: 72%
“…It appears that both the intrinsic and the extrinsic pathway are involved in stenodactylin-induced cell death, reinforcing the idea that RIPs induce a complex response in intoxicated cells triggering multiple death pathways (Polito et al, 2009;Pervaiz et al, 2016). Furthermore, it has been recently reported that abrin, another type 2 RIP, can trigger cell death through many mechanisms in different cell lines (Tiwari and Karande, 2019). Stenodactylin treatment induces the disruption of mitochondrial membrane potential, as confirmed by JC-1 positive staining at 24 h. RIP-triggered mitochondria-associated apoptotic signaling was also previously described (Narayanan et al, 2005;Sikriwal et al, 2008;Bora et al, 2010;Polito et al, 2016c).…”
Section: Discussionmentioning
confidence: 72%
“…This represents a fundamental requirement in anti-cancer therapy, since the use of drugs, able to trigger multiple death pathways, can avoid the selection of resistant clones. Further studies will be necessary to identify the involvement of autophagy and/or endoplasmic reticulum stress, which have been already described for some RIPs [ 16 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%